Cutibacterium acnes clonal complexes display various growth rates in blood culture vials used for diagnosing orthopedic device-related infections. (December 2021) - El Sayed, Faten; Jeverica, Samo; Roux, Anne-Laure; Bauer, Thomas; Nkam, Lionelle; Sivadon-Tardy, Valérie; Noussair, Latifa; Herrmann, Jean-Louis; Gaillard, Jean-Louis; Rak, Mitja; Papst, Lea; Rottman, Martin
Abstract: Objectives: Blood culture bottles (BCBs) are commonly used for the diagnosis of infections associated with orthopedic devices. Although Cutibacterium acnes is an important pathogen in orthopedics, relatively little is known about its growth characteristics in BCBs. This prompted us to analyze the influence of bacterial genotype and clinical significance on time-to-detection (TTD) in BCBs. Methods: We reviewed 59 cases of orthopedic device-related infections in which at least one intraoperative specimen yielded a pure C. acnes culture from anaerobic BCBs (BD Bactec Lytic/10 Anaerobic/F; Lytic-Ana) and/or solid media. A strain was considered infectant if the same genotype was present in two or more intraoperative samples. From these cases, we isolated a total of 72 unique C. acnes strains belonging to four multilocus sequence type clonal complexes (CCs): CC18, CC28, CC36 and CC53. Growth rate and TTD in Lytic-Ana BCB were studied under experimental conditions (inoculation of standard inoculum) and in clinical samples (inoculation of periprosthetic tissue samples). Results: Median TTD values were shorter for CC53 compared to other CCs under experimental conditions (69 vs. 103 h; p < 0.001) and from clinical specimens (70 vs. 200 h; p = 0.02). Infectant strains had a shorter median TTD compared to contaminant strains in a clinical situation, while the difference was not observed under experimental conditions. Conclusions: The detection dynamics of C. acnes in Lytic-Ana BCBs were associated with genotype. Thus, TTD not only reflects the bacterial load in clinical samples, but may also reflect the intrinsic properties of the clonal complex of C. acnes . Highlights: Diagnosis of C. acnes orthopedic device-related infections (ODRI) is challenging. Blood culture systems are increasingly used for the culture of ODRI specimens. C. acnes clonal complex (CC) affects growth rate in Lytic-Ana blood culture media. Clonal complex (CC)53 grew faster than non-CC53 C. acnes in Lytic-Ana.